EFEKTIVITAS MENGONSUMSI OBAT ANTIRETROVIRAL DALAM MENURUNKAN ANGKA VIRAL LOAD PADA ODHA - Fahrani, Chantika Lailatussa'adah; Romadi, Romadi; Nuswantoro, Ari; Wahdaniah, Wahdaniah; Aditia, Aditia (Media Penelitian dan Pengembangan Kesehatan, 2023)
Human Immunodeficiency Virus (HIV) has infected many people throughout the world. In Indonesia alone, around 540,000 people have been infected with HIV and are living with Acquired Immunodeficiency Syndrome (AIDS). Until now, antiretroviral drug therapy (ARV) is the best choice which aims to reduce the risk of transmission, prevent worsening due to opportunistic infections, improve the quality of life of sufferers, and reduce the amount of virus (viral load) in the blood until it is undetectable. The aim of this study was to explain the effectiveness of taking ARV drugs in reducing viral load rates in patients at the Tulipe Clinic, M. Th. Hospital. Djaman, Sanggau Regency. This is a non-experimental quantitative research with a cross-sectional design. Sampling technique using purposive sampling, with the criteria applied, namely that respondents are ODHA or patients who have been diagnosed with HIV/AIDS, have undergone ARV therapy for at least six months, and are willing to become respondents so that a total of 89 people during 2022 – 2023 were obtained. The results of the study showed that the duration of taking ARVs ranged from 6 to 98 months, the viral load number was 14 - 35,400 copies/ml. The Spearman test obtained a significance value of 0.000 (p < 0.05), which means that taking ARV medication is effective in reducing viral load rates in Tulipe Clinic patients at M. Th. Hospital. Djaman, Sanggau Regency. Based on the results, it is expected that future studies can measure viral load along with molecular immunological parameters such as cytokine and antibody levels.